Encapsulation of β-NGF in injectable microrods for localized delivery accelerates endochondral fracture repair - Rivera, Kevin O.; Cuylear, Darnell L.; Duke, Victoria R.; O’Hara, Kelsey M.; Zhong, Justin X.; Elghazali, Nafisa A.; Finbloom, Joel A.; Kharbikar, Bhushan N.; Kryger, Alex N.; Miclau, Theodore; Marcucio, Ralph S.; Bahney, Chelsea S.; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Currently, there are no non-surgical FDA-approved biological approaches to accelerate fracture repair. Injectable therapies designed to stimulate bone healing represent an exciting alternative to surgically implanted biologics, however, the translation of effective osteoinductive therapies remains challenging due to the need for safe and effective drug delivery. Hydrogel-based microparticles platforms may be a clinically relevant solution to create controlled and localized drug delivery to treat bone fractures. Here, we describe poly (ethylene glycol) dimethacrylate (PEGDMA)-based microparticles, in the shape of microrods, loaded with beta nerve growth factor (β-NGF) for the purpose of promoting fracture repair. In vitro release studies showed there is significant retention of protein within the polymer matrix over 168 hours through physicochemical interactions. Bioactivity of protein post-loading was confirmed with the TF-1 tyrosine receptor kinase A (Trk-A) expressing cell line. In vivo studies using our well-established murine tibia fracture model show that PEGDMA microrods injected at the site of fracture remained adjacent to the callus for over 7 days. Importantly, a single injection of β-NGF-loaded PEGDMA microrods resulted in improved fracture healing as indicated by a significant increase in the percent bone in the fracture callus, trabecular connective density, and bone mineral density relative to soluble β-NGF control indicating improved drug retention within the tissue. The concomitant decrease in cartilage fraction supports our prior work showing that β-NGF promotes endochondral conversion of cartilage to bone to accelerate healing. In conclusion, we demonstrate a novel and translational method wherein β-NGF can be encapsulated within PEGDMA microrods for local delivery and that β-NGF bioactivity is maintained resulting in improved bone fracture repair.